Ngabubuteach: Membangun Kepedulian Sosial dan Kemampuan Bahasa Inggris Melalui Pengabdian Masyarakat di Panti Asuhan Al-Madinah Wara - Que, Stella Rose; Ngadjen, Syahdania Aini; Notanubun, Fitri Faradila (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2025)
The “Ngabubuteach” community service activity was carried out to improve the English language skills of the children at the Al-Madinah Wara Orphanage while also fostering social awareness and concern for the community among students. This program was designed with an interactive learning approach through educational games, conversation simulations, and fun group activities to motivate the children to use English. The activity consisted of four main stages, namely fundraising to support the needs of the activity, preparation of teaching materials, implementation of the learning process, and evaluation to measure learning outcomes. Based on the evaluation results, the children showed an improvement in their ability to understand basic vocabulary, greetings, and simple expressions in English. Meanwhile, the students involved gained valuable experience in teaching practice, teamwork, and strengthening social empathy towards others. The success of this activity was due to the collaboration between student organizations, the support of supervising lecturers, and the cooperation of the orphanage. In the future, this program is expected to develop more varied materials and provide more adequate learning facilities.